Design, synthesis of flavokawain b derivative and their cytotoxic effects on MCF-7 and MDA-MB-231 cell lines - Addila, Abu Bakar (2018)
Cancer is among the cause of death whereof breast cancer is the second leading cause of cancer death among women worldwide. Cancer treatment with standard anti-cancer drug, chemotherapy and radiation have caused unwanted side effects in the patient. Therefore chalcone with many pharmacological benefits such as anti-cancer, anti-mitotic, etc., has gained attention as a subject of research. Flavokawain B derivative chalcones bearing methoxy, dimethoxy, trimethoxy, bromo, chloro, fluoro, methyl, methylthio, nitro, hydroxyl and dimethylamino groups on benzaldehyde were synthesized via Claisen-Schmidt condensation method using base catalyst; the synthesized compounds were characterized by using UV-Visible, Fourier Transform Infrared spectrophotometry (FTIR), Gas Chromatography-Mass Spectrometry (GC-MS) and Nuclear Magnetic Resonance (NMR) spectrometry and evaluated for their cytotoxicity against breast cancer cell line by using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay in vitro. Among 22 synthesized compounds, two compounds, 80 and 91 have been discovered as new flavokawain B analogs and some compounds showed good anti-cancer activity following the cut-off point value, IC50 is less than 30 μg/mL. The compounds are chalcone 4 (7.70 ± 0.30 μg/mL), 5 (8.90 ± 0.60 μg/mL), 75 (12.30 ± 1.40 μg/mL), 79 (6.50 ± 0.40 μg/mL), 80 (7.12 ± 0.80 μg/mL), 82 (9.70 ± 0.70 μg/mL), 84 (5.50 ± 0.35 μg/mL), 85 (8.43 ± 0.40 μg/mL), 44 (13.30 ± 3.10 μg/mL) and 91 (6.50 ± 0.35 μg/mL) that exhibited good anti-cancer activity against MCF-7. Chalcone 4 (5.90 ± 0.30 μg/mL), 5 (6.80 ± 0.45 μg/mL), 75 (18.10 ± 1.10 μg/mL), 79 (4.12 ± 0.20 μg/mL), 80 (4.04 ± 0.30 μg/mL), 81 (9.50 ± 0.60 μg/mL), 82 (8.30 ± 0.56 μg/mL), 84 (5.50 ± 0.40 μg/mL), 85 (7.22 ± 0.70 μg/mL) and 44 (17.10 ± 2.15 μg/mL) showed good anti-cancer activity against MDA-MB-231 as well as compound 79 and 80 was discovered to be more active than the reference drug doxorubicin (5.05 ± 0.20 μg/mL). Structure-activity relationship study suggested that significantly improved cytotoxicity was shown by halogenated flavokawain B, followed by methoxylated flavokawain B, particularly when substitution occurred at position 2 and 3 in ring B.